Wellsina Mite Hemicheyletia wellsina (De Leon) (Arachnida: Acari: Cheyletidae) - Haleigh A. Ray; Marjorie A. Hoy (EDIS, 2015)
This predatory mite was recently discovered in an unsprayed greenhouse at the University of Florida, Gainesville, living on Phalaenopsis and Dendrobium orchids, and assumed to be feeding on orchid pests such as spider mites, tenuipalpid mites, and mealybugs that were present on the orchids. Because there was no published information on this species as a natural enemy of orchid pests, colonies were initiated here to study its biology, maintained on two-spotted spider mite prey. Hemicheyletia wellsina does not appear likely to be an effective natural enemy in agricultural crops as an introduced predator, but could be beneficial in natural biological control in natural ecosystems, where pest densities are lower. This 5-page fact sheet was written by Haleigh A. Ray and Marjorie A. Hoy, and published by the UF Department of Entomology and Nematology, December 2014. (Photo: Haleigh Ray, UF/IFAS)